2016 International Water Safty Symposium - 윤종주 (충남연구원, 2016)
Background - Accidental Rip currents ●The social issue at the Haeundae beach ●Rip currents occur repeatedly and sweep away swimmers ●Rip currents are generated due to the longshore variations of wave energy caused by alongshore non-uniformities ●Strong jet-like flow evolves through the lower-energy zone (rip-channel) Accidental Rip currents - 이후 생략